In vitro plant regeneration and cryopreservation of Arachis glabrata (Fabaceae) using leaflet explants - Dolce, Natalia Raquel (2017)
Fil: Dolce, Natalia Raquel. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.